The voluntary Code of conduct on invasive alien plants in Belgium: results and lessons learned from the AlterIAS LIFE+ project. (26th June 2014) - Halford, M.; Heemers, L.; van Wesemael, D.; Mathys, C.; Wallens, S.; Branquart, E.; Vanderhoeven, S.; Monty, A.; Mahy, G.
<x xml:space="preserve">Abstract</x> Voluntary approaches have been recently used in the horticultural sector to deal with the introduction and spread of invasive alien plants. In Belgium, the first Code of conduct has been developed within the frame of the AlterIAS project, a LIFE+ "Information & Communication" project aiming at raising the awareness of horticulture professionals and gardeners on the invasive plants issue. The Belgian Code was prepared in consultation with representatives from the ornamental sector, public authorities and the scientific community. The Code was promoted throughout the country with a specific communication campaign entitled "Plant different". Thanks to communication efforts, a positive dynamic of involvement was observed over time. Surveys were performed to assess the changes of attitudes and the perception of the Code by the target audience of the project. Positive results were achieved for horticulture professionals. However, the Code will require more time to be widely adopted by the ornamental sector in Belgium.